Standards of teeth preparations for anterior resin bonded all-ceramic crowns in private dental practice in Jordan (Journal of Applied Oral Science, 2011)
OBJECTIVES: To investigate if general dental practitioners (GDPs) in private practice in Jordan follow universal guidelines for preparation of anterior teeth for resin bonded all-ceramic crowns (RBCs). MATERIAL AND METHODS: A sample (n=100) of laboratory models containing 208 tooth preparations for IPS Empress and In Ceram, featuring work from different GDPs, was obtained from 8 commercial dental laboratories. Aspects of preparations were quantified and compared with accepted criteria defined following a review of the literature and recommendations of the manufactures' guidelines. RESULTS: Subgingival margins on the buccal aspect were noticed in 36% of the preparations, 54% demonstrated overpreparation with a tendency to overprepare the teeth on the mesiodistal plane more than buccolingual plane. Twenty percent of samples presented a shoulder finish line while a chamfer margin design was noticed in 39%. Twenty-nine percent and 12% of samples had either a feathered or no clear margin design respectively. Incisal underpreparation was observed in 18% of dies of each type. Only 17% of all preparations were found to follow the recommended anatomical labial preparations while 29% of the RBC preparations were found to have the recommended axial convergence angle. In total, 43% of preparations were found to have the recommended depth of the finish line. CONCLUSIONS: It was found that relevant guidelines for RBC preparations were not being fully adhered to in private practice in Jordan.